Risk of small intestinal bacterial overgrowth in patients receiving proton pump inhibitors versus proton pump inhibitors plus prokinetics. Issue 2 (2nd April 2018) - Revaiah, Pruthvi C; Kochhar, Rakesh; Rana, Surinder V; Berry, Neha; Ashat, Munish; Dhaka, Narendra; Rami Reddy, Y; Sinha, Saroj K
Abstract : Background and Aim: Intestinal dysmotility is considered a risk factor for small intestinal bacterial overgrowth (SIBO). Prokinetics improve intestinal motility and are often prescribed with proton pump inhibitors (PPIs) in patients with gastroesophageal reflux disease (GERD) and/or functional dyspepsia. The present study aimed to evaluate the prevalence of SIBO and the orocecal transit time (OCTT) in patients taking PPI compared with those taking PPI plus prokinetics. Methods: The study is a single‐center, cross‐sectional study. Enrolled patients (with age > 12 years) were divided into two groups: patients taking PPIs for more than 3 months (Group A) and those taking PPIs with prokinetics for more than 3 months (Group B) for various indications. Lactulose breath test (LBT) for OCTT and glucose breath test (GBT) for SIBO were conducted for all patients. Results: Of the 147 enrolled patients, SIBO was documented in 13.2% patients in Group A versus 1.8% in Group B, P = 0.018. Median OCTT in Group A was 130 (105–160) min compared with 120 (92.5–147.5) min in Group B ( P = 0.010). Median OCTT among SIBO‐positive patients was 160 (140–172.5) min compared with SIBO‐negative patients, where it was 120 (103.75–150) min ( P = 0.002). The duration and type of PPI used were not associated with the occurrence of SIBO in our study. Conclusion: The use of prokinetics in patients on PPI may reduce the risk of SIBO by enhancing intestinal motility and may reduce SIBO risk associated with long‐term PPI use. Abstract : Addition of prokinetics to patients on proton pump inhibitor (PPI) may reduce the risk of small intestinal bacterial overgrowth (SIBO) by enhancing intestinal motility and may reduce SIBO risk associated with long‐term PPI use. SIBO was documented in 13.2% patients in PPI group versus 1.8% in PPI plus prokinetic group, P = 0.018.